OPTIMIZATION OF RETENTION POND IN FLOOD CONTROL EFFORTS IN PEKANBARU (URBAN FLOOD SYSTEM IMPROVEMENT PROJECT) - Erni Yulianti; Eko Prasetyo (Bajang Institute, 2024)
This research aims to optimize the function of retention ponds as part of the urban flood control improvement project in Pekanbaru. Evaluation was conducted on the capacity and efficiency of retention ponds, with a focus on spatial distribution, sustainability, and environmental impact. The findings of this study provide a foundation for formulating concrete and data-driven improvement recommendations. The spatial distribution of retention ponds is crucial in understanding their effectiveness in mitigating flood risks. Evaluation of the actual capacity of retention ponds provides an overview of their ability to accommodate excess rainwater, while efficiency identifies factors for enhancement and improvement. Improvement recommendations include increasing capacity, implementing advanced technology, and developing data-driven solutions. Involving stakeholders, including local government, research institutions, and the community, is a strategic step to ensure successful implementation. The application of sensors and geographic information systems (GIS) can enhance the effectiveness of retention pond operational management. Sustainability of solutions is realized through routine maintenance, performance monitoring, and multi-stakeholder collaboration. This research significantly contributes to urban flood management in Pekanbaru by providing concrete, data-driven recommendations for the retention pond system.